Doing Privatization Right - Jones, Leroy; Jammal, Yahya; Gökgür, Nilgün; Kikeri, Sunita (World Bank, Washington, DC, 2012)
A recent study examining privatization results in four Sub-Saharan African countries yielded two broad conclusions: First, privatization is not easy to do, and getting it right can be tough in low-income countries. Second, if privatization is done right and there is a little luck, it can lead to substantial welfare gains that are reasonably and equitably distributed across stakeholders, consumers, workers, governments, and owners or operators.